2019
DOI: 10.1039/c8ra08943d
|View full text |Cite
|
Sign up to set email alerts
|

Photoisomerization and thermal isomerization of ruthenium aqua complexes with chloro-substituted asymmetric bidentate ligands

Abstract: Introduction of a chloro substituent to the bidentate ligand of ruthenium aqua complexes enhanced photoisomerization and thermal back-isomerization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…However, the effect of intramolecular hydrogen bonding on photosubstitution reactions has yet to be investigated. We previously reported the photoisomerization of Ru­(II) aqua complexes with tridentate ligands and asymmetric bidentate ligands, showing that intramolecular hydrogen bonding played an important role in determining the reversibility of the photoisomerization, as depicted in Figure a. Irreversible photoisomerization was observed from distal -[Ru­(tpy)­(pynp)­OH 2 ] 2+ to the proximal isomer (tpy = 2,2′:6′,2″-terpyridine, pynp = 2-(2′-pyridyl)-1,8-naphthyridine), where intramolecular hydrogen bonding occurs between the aqua ligand and a nitrogen atom on the pendant moiety of the pynp ligand.…”
Section: Introductionmentioning
confidence: 99%
“…However, the effect of intramolecular hydrogen bonding on photosubstitution reactions has yet to be investigated. We previously reported the photoisomerization of Ru­(II) aqua complexes with tridentate ligands and asymmetric bidentate ligands, showing that intramolecular hydrogen bonding played an important role in determining the reversibility of the photoisomerization, as depicted in Figure a. Irreversible photoisomerization was observed from distal -[Ru­(tpy)­(pynp)­OH 2 ] 2+ to the proximal isomer (tpy = 2,2′:6′,2″-terpyridine, pynp = 2-(2′-pyridyl)-1,8-naphthyridine), where intramolecular hydrogen bonding occurs between the aqua ligand and a nitrogen atom on the pendant moiety of the pynp ligand.…”
Section: Introductionmentioning
confidence: 99%
“…42−44 The introduction of a substituent near the metal center enhances the quantum yields of photoisomerization and allows thermal back isomerization from the distal to proximal isomer. 44 We have reported applications of these stimuliresponsive complexes to artificial photosynthesis, 45−47 stimulus-responsive giant vesicles, 48 host−guest systems. 13 In this work, we focused on the ruthenium complex, proximal-[Ru(C 10 tpy)(C 10 pyqu) OH 2 ] 2+ (proximal-1), that responds to light and thermal stimuli (C 10 tpy = 4′-decyloxy-2,2′:6′,2″-terpyridine and C 10 pyqu = 2-[2′-(6′-decyloxy)pyridyl]quinoline).…”
Section: Introductionmentioning
confidence: 99%
“…We have studied photoresponsive ruthenium aqua complexes with tridentate and asymmetric bidentate ligands. The introduction of a substituent near the metal center enhances the quantum yields of photoisomerization and allows thermal back isomerization from the distal to proximal isomer . We have reported applications of these stimuli-responsive complexes to artificial photosynthesis, stimulus-responsive giant vesicles, host–guest systems …”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] We have studied such systems and have previously reported that thermal back-isomerization can be achieved by introducing steric hindrance near the metal center. 19 The major difference between photoresponsive organic molecules and metal complexes lies in their functionality. In organic photochromic molecular systems, the switchable sites only cause structural changes and have no further functionality.…”
Section: Introductionmentioning
confidence: 99%